2011
DOI: 10.1002/mc.20752
|View full text |Cite
|
Sign up to set email alerts
|

Nifedipine synergizes with calcium in activating the calcium sensing receptor, suppressing the expression of thymidylate synthase and survivin and promoting sensitivity to fluorouracil in human colon carcinoma cells

Abstract: We have previously reported that activation of the G protein coupled calcium-sensing receptor (CaSR) by extracellular Ca(2+) down-modulates the expression of thymidylate synthase (TS) and survivin and promotes sensitivity to fluorouracil in human colon carcinoma cells. Here, we report for the first time that the cardiac drug nifedipine acted synergistically with Ca(2+) in CaSR activation and in the induction of intracellular Ca(2+). Nifedipine in combination with Ca(2+) significantly down-modulated the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…These results coincide with those of a previous study obtained using colon, breast, and renal cell carcinomas [9,11,13,14,17,18]. Loss of CaSR expression activates a myriad of stem cell-like molecular features that drive and sustain the carcinomas and drugresistant phenotypes of colon cancer [10,19]. CaSR might regulate the differentiation of colonic epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…These results coincide with those of a previous study obtained using colon, breast, and renal cell carcinomas [9,11,13,14,17,18]. Loss of CaSR expression activates a myriad of stem cell-like molecular features that drive and sustain the carcinomas and drugresistant phenotypes of colon cancer [10,19]. CaSR might regulate the differentiation of colonic epithelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies have demonstrated that calcium-induced growth suppression depends on the activation of CaSR [14, 15, 17]. This is associated with differentiation and depends on a transient rise in the level of intracellular calcium [35]. Based on these past data, we hypothesized that exposure of the colonic epithelial cells to gadolinium in conjunction with calcium would induce a rise in intracellular calcium over that seen with calcium alone.…”
Section: Discussionmentioning
confidence: 99%
“…CaSR promotes the expression of the tumor suppressor E‐cadherin 12–14. It up‐regulates the expression of the growth‐inhibitory and differentiation related p21/Waf1 cell cycle check point protein; up‐regulates the expression of γ‐catenin and p27; suppresses the malignancy associated β‐catenin/Wnt, c‐myc and cyclin D1 pathways12–15 and suppresses the expression of thymidylate synthase (TS) and survivin 16, 17, 19. Some of these pathways have been validated by immunohistochemical analysis of histological sections of normal human colon and colon tumor 15.…”
mentioning
confidence: 99%
“…A high level of survivin expression blocks the ease in which cell death occur in response to treatment with anticancer drugs and a high level of survivin expression is associated with cytotoxic drug resistance in many types of cancer 26–28. CaSR suppresses the expression of both TS and survivin and promotes a dramatic increase in the cytotoxic response to 5‐FU 16, 17, 19…”
mentioning
confidence: 99%